700. Ampicillin-Ceftriaxone Versus Ampicillin-Gentamicin for Definitive Therapy of Enterococcus faecalis Infective Endocarditis: A Propensity Score-Matched, Retrospective Cohort Analysis. (31st December 2020) - Shah, Niyati H; Shutt, Kathleen A; Doi, Yohei; Doi, Yohei
Abstract: Background: The mortality rate for Enterococcus faecalis infective endocarditis (EIE) is high. Ampicillin-ceftriaxone (AC) has emerged as an alternative antibiotic regimen with lower toxicity compared to ampicillin-gentamicin (AG), but evidence regarding its success in reducing EIE-associated mortality in the United States is limited. We retrospectively compared mortality in EIE patients treated with AG versus AC. Methods: We conducted a retrospective, propensity score-matched, cohort analysis of EIE patients treated with AG or AC from 2010 to 2017 at three hospitals in Pittsburgh, Pennsylvania. Patients were included in the analysis if they were treated for EIE with either AC or AG as the pathogen-directed antibiotic regimen for at least forty-eight hours. We assessed 90-day mortality as the primary outcome, and in-hospital mortality, length of hospital stay, hospital readmissions, adverse events, and relapse of bacteremia as the secondary outcomes. Results: A total of 190 patients with EIE (100 treated with AC and 90 with AG) were included. Ninety-day mortality was significantly higher in the AC group than the AG group (21% vs 8%, p = 0.02). After propensity score-matching, 56 patients in each group remained for the outcomes analysis. We observed similar rates of 90-day mortality (6% vs 4%, p = 0.55), bacteremia relapse (0 patients in both cohorts), treatment failure (0% vs 1%, p = 0.50), and 90-day hospital readmission (24% vs 23%, p = 0.85) in the AC and AG-treated patient cohorts. Adverse events were more common in patients treated with AG, and more patients in the AG cohort switched antibiotic regimens than in the AC group. Conclusion: EIE patients treated with AC have similar mortality rates as those treated with AG, while AG is associated with increased toxicity and adverse events. Larger, multi-center studies are still needed to compare the two antibiotic regimens. Disclosures: All Authors : No reported disclosures